Study on the Manufacturing Process of Low Temperature Ductile Iron Casting Gear Box Used for Locomotive - Kuang Yi; Fan Naize; Tian Huajun; Pei Bang; Zhao Jiadong; Ning Ke; Zhang Xiangru; Xu Sen; Xu Hui (Jixie chuandong)
Taking the QT400-18 L low temperature ductile iron gear box used for locomotive as example,through the control of the element content of the material,the graphite spheroidization is more fully. At the same time,the samples are heat treated to ensure the stability of mechanical property. In the casting process,the casting process is improved to reduce the casting defects and to ensure the surface quality of the products.